The Practice of Buying and Selling Fish with a Tariff System in Fishing Islamic Law Perspective - Sahman Z (Walidem Institute and Publishing (WIP), 2023)
This study aims to analyze the practice of buying and selling fish with a tariff fishing rod system using an Islamic legal approach. This research was conducted in Sidowayah Village, Polanharjo District, Klaten Regency. This research is a type of field research with a qualitative descriptive approach. Data were collected using interview and observation methods at fishing grounds. Then the data obtained are analyzed descriptively to obtain conclusions in the study. The results of this study show that the practice of tariff fishing in Sidowayah Village, if viewed in terms of Islamic law, should not be carried out, because it contains elements prohibited in Islam, especially in the chapter of Fiqh Muamalah. After all, this practice contains elements of gharar (obscurity) in the object of contract and maisir (luck) which is unclear in terms of quality and quantity due to the absence of a checking process first. Therefore, it would be nice to avoid this kind of buying and selling so that the buying and selling that is done is valid under Islamic law.